Interest rate in Oman: is it fair?. Issue 3 (10th August 2015) - Al-Muharrami, Saeed
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this study is to try to answer whether the banking system in Oman is fair for both depositors and entrepreneurs. Design/methodology/approach – The interest margin decomposition is based on the methodology proposed in Randall (1998). The income statement of banks defines profits before taxes (P) as interest income (II), plus non-interest income (NII), minus interest expense (IP), minus operating costs (OC) and minus provision for loan losses (Prov). After rearranging this identity, the net interest revenue can be expressed as follows: II – IP = OC + Prov + P – NII. The above expression decomposes the margin into the following cost and profit components: reserve requirement costs, operational costs, loan loss provision costs, profitability and non-interest income (with a negative sign). Findings – A trend analysis of commercial banks' interest rate spreads in Oman exposes the following facts: First, the implicit interest margin is relatively small (in the neighborhood of 1 percentage point); second, profits constitute a substantial proportion of the margin; third, the share of operating costs in the margin has been broadly constant over time; fourth, reserve requirement costs have been reduced following the decline of the reserve requirement ratio; and fifth, the weighted average interest rate on deposits base is lower than the rate of inflation. Originality/value – This work is original.